Traditional folk event with national importance: The impact of visitors’ age - Petra Solarová; Roman Švec (DETUROPE)
In the context of the cultural tourism, this paper focuses on the traditional folk event with national importance that is held in the Czech Republic and its name is Porta. The aim is to assess characteristic traits and satisfaction of two age categories of Porta´s visitors. Through the realised research among visitors, the importance of segmentation was proved. Hence, it is crucial to focus on getting to know the visitors and their motivation. In addition to that, cultural events are also important for local government. According to the officials of local government, where this event is held, such events are able to attract visitors to the particular locality. However, they have only limited opportunities how to support these events (especially from the financial viewpoint).